Hsp70 and larval thermotolerance in Drosophila melanogaster: How much is enough and when is more too much? - Krebs, R.A.; Feder, M.E. (Journal of Insect Physiology, 1998)
Heat shock proteins (Hsps) and other molecular chaperones perform diverse cellular roles (e.g., inducible thermotolerance) whose functional consequences are concentration dependent. We manipulated Hsp70 concentration quantitatively in intact larvae of Drosophila melanogaster to examine its effect on survival, developmental time and tissue damage after heat shock. Larvae of an extra-copy strain, which has 22 hsp70 copies, produced Hsp70 more rapidly and to higher concentrations than larvae of a control strain, which has the wild-type 10 copies of the gene. Increasing the magnitude and duration of pretreatment increased Hsp70 concentrations, improved tolerance of more severe stress, and reduced delays in development. Pretreatment, however, did not protect against acute tissue damage. For larvae provided a brief or mild intensity pretreatment, faster expression of Hsp70 in the extra-copy strain improved survival to adult and reduced tissue damage 21h after heat shock. Negative effects on survival ensued in extra-copy larvae pretreated most intensely, but their overexpression of Hsp70 did not increase tissue damage. Because rapid expression to yield a low Hsp70 concentration benefits larvae but overexpression harms them, natural selection may balance benefits and costs of high and low expression levels in natural populations.